Peningkatan Kualitas Aplikasi dengan Pengujian Fungsional Menggunakan Robot Framework - David Kurniawan; Muhammad Chandra; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Functional testing is an important stage in aplikasi development cycle aimed at ensuring that the application works correctly and meets the specifications. However, manual functional testing can be a tiring task and prone to human errors. Therefore, this research attempts to improve aplikasi quality by using Robot Framework as an automated functional testing tool. Robot Framework is an open-source automated testing framework that can be used to test desktop and web applications easily. The research method used is an experiment comparing the results of manual and automated functional testing on the same application. The results show that automated functional testing with Robot Framework can reduce the time required for testing, improve testing efficiency, and produce more accurate testing reports. Therefore, the use of Robot Framework as a functional testing tool can improve aplikasi quality by reducing human errors and improving testing efficiency.